2018
DOI: 10.2217/bmm-2017-0273
|View full text |Cite
|
Sign up to set email alerts
|

Investigating MIRNA-661 and ATG4-B MRNA Expression as Potential Biomarkers for Hepatocellular Carcinoma

Abstract: Our data are the first report of its kind regarding the considerable clinical significance of miR-661 and ATG-4B mRNA in HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Among those, more than 60% (14/23) of the genes showed an independent impact on overall survival in the TCGA-LIHC cohort as revealed by multivariate analyses ( Figure 5D and Supplemental Tables 11 and 12 ). Importantly, only a few genes were previously implicated with liver cancer development (ATG4B, CCR5, MCM6, and UCN ) ( 26 29 ), whereas most of the epidrivers were newly identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those, more than 60% (14/23) of the genes showed an independent impact on overall survival in the TCGA-LIHC cohort as revealed by multivariate analyses ( Figure 5D and Supplemental Tables 11 and 12 ). Importantly, only a few genes were previously implicated with liver cancer development (ATG4B, CCR5, MCM6, and UCN ) ( 26 29 ), whereas most of the epidrivers were newly identified.…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathway analyses of the putative epi-drivers further centered on molecular mechanisms of cancer, cell survival, proliferation and invasion as well as stem cell activation and immune regulation (Supplemental Figure 5B). While some genes (ATG4B, CCR5, MCM6, UCN) were detected in the context hepatocarcinogenesis before, most of the epi-drivers were result of the investigation of our unique cohort (26)(27)(28)(29).…”
Section: Identification and Validation Of Epi-drivers In Hcc Development And Progressionmentioning
confidence: 99%
“…At present, there are only few studies of this miRNA and its relationship to cancer. A study by Ali et al revealed that the combined analysis of hsa-miR-661-3p and ATG-4B gene content could be a marker for clinical diagnosis and prognosis of liver cancer (31). In addition, it has been reported that hsa-miR-661-3p played an important role in the maintenance of redox and metabolic balance of intestinal cancer cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐34a, miR‐34c, miR‐449a, miR‐449‐5p, and miR‐665‐3p can target ATG4B, affecting autophagy in various pathological processes 42–50 . Additionally, miR‐16, miR24‐2, miR‐34c‐5p, and miR‐661 increase the protein levels of ATG4B to activate cytoprotective autophagy in the development of diverse tumors 51–54 . MiR‐129‐3p enhances intracellular BCG survival by repressing autophagy via ATG4B 55 .…”
Section: The Regulatory Factors Of Atg4mentioning
confidence: 99%
“…For example, Luo et al reported that BOLA2 is closely associated with both the activation of p62‐Keap1 signaling and ATG4B expression according to Gene Expression Profiling Interactive Analysis in a training cohort of HCC samples 125 . Likewise, the expression levels of miR‐661 and ATG4B through bioinformatics‐based selection were higher in the HCC serum group than in the healthy control group 54 . Additionally, heat shock transcription factor 1 (HSF1) and early growth response factor (Egr‐1) elevate ATG4B levels by promoting its transcription through binding to the ATG4B gene promotor region.…”
Section: Atg4 and Diseasesmentioning
confidence: 99%